Die "Confessio Augustana" im ökumenischen Gespräch - Frank, Günter; Leppin, Volker; Licht, Tobias (De Gruyter, 2021)
The year 2030 will mark the 500th anniversary of the Augustan Confession, the most important confessional document from the Wittenberg Evangelical movement. Written by Melanchthon as his last attempt to preserve the unity of Western Christianity while defending overdue reforms, it became a document of contemporary division. Can the ecumenical movement in its present form find a way to access the text together?